Transcriptomic analysis of Rhizobium leguminosarum bacteroids in determinate and indeterminate nodules - Green, RT; East, A; Karunakaran, R; Downie, JA; Poole, PS (Microbiology Society, 2019)
Two common classes of nitrogen-fixing legume root nodules are those that have determinate or indeterminate meristems, as in Phaseolus bean and pea, respectively. In indeterminate nodules, rhizobia terminally differentiate into bacteroids with endoreduplicated genomes, whereas bacteroids from determinate nodules are less differentiated and can regrow. We used RNA sequencing to compare bacteroid gene expression in determinate and indeterminate nodules using two Rhizobium leguminosarum strains whose genomes differ due to replacement of the symbiosis (Sym) plasmid pRP2 (strain Rlp4292) with pRL1 (strain RlvA34), thereby switching symbiosis hosts from Phaseolus bean (determinate nodules) to pea (indeterminate nodules). Both bacteroid types have gene expression patterns typical of a stringent response, a stressful environment and catabolism of dicarboxylates, formate, amino acids and quaternary amines. Gene expression patterns were indicative that bean bacteroids were more limited for phosphate, sulphate and iron than pea bacteroids. Bean bacteroids had higher levels of expression of genes whose products are predicted to be associated with metabolite detoxification or export. Pea bacteroids had increased expression of genes associated with DNA replication, membrane synthesis and the TCA (tricarboxylic acid) cycle. Analysis of bacteroid-specific transporter genes was indicative of distinct differences in sugars and other compounds in the two nodule environments. Cell division genes were down-regulated in pea but not bean bacteroids, while DNA synthesis was increased in pea bacteroids. This is consistent with endoreduplication of pea bacteroids and their failure to regrow once nodules senesce.